Stray studies on mushrooms from China - Yang, Kun L.; Lin, Jia Y.; Li, Guang-Mei (Phytotaxa, 2026)
This study presents taxonomic updates and revisions on mushrooms from China, incorporating morphological, traditional phylogenetic, and phylogenomic approaches. In Kingdom Amoebozoa, several taxa of Ceratiomyxa and Tubifera are discussed. In Ascomycota of Kingdom Fungi, two species of Geoglossum and Squamulea with special morphology or ecology are reported. In Basidiomycota, Kingdom Fungi, some cryptic taxa are recognized with molecular evidence for Agaricus, Amanita, Calvatia, Cantonopsathyra, Clavaria s. l., Delicatula, Disciseda, Geastrum, Lepiota, Leucocoprinus s. l., Mycena s. l., Mycoamaranthus, Pseudolyophyllum and Volvariella. These are described, and some new combinations in Lycoperdaceae and Mycenaceae are suggested to achieve monophyly. A reclassification is presented for the leucocoprinoid group, organizing two subfamilies and nine genera (Leucocoprinoideae including Leucocoprinus, Leucoagaricus, Conioexocarpus, Pulchrolepiota and Tristolepiota; and Micropsalliotoideae including Micropsalliota, Mesopsalliota, Macropsalliota and Candelolepiota). Concept of the historical species name Macropsalliota purpureorubra is clarified with recent collections. Sinotermitomyces meipengianus is surprisingly recognized as an earlier name of Macrolepiota detersa based on type studies, and is recombined as Macrolepiota meipengiana.